If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 183 = 83 + k Solving 183 = 83 + k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. 183 + -1k = 83 + k + -1k Combine like terms: k + -1k = 0 183 + -1k = 83 + 0 183 + -1k = 83 Add '-183' to each side of the equation. 183 + -183 + -1k = 83 + -183 Combine like terms: 183 + -183 = 0 0 + -1k = 83 + -183 -1k = 83 + -183 Combine like terms: 83 + -183 = -100 -1k = -100 Divide each side by '-1'. k = 100 Simplifying k = 100
| -1/3x^2+5=0 | | ln(7x+2)=ln(5x-14) | | 21/3/8 | | 231=62+s | | 6x+68=7x+13 | | 123=-282+a | | 2(x)+9=15 | | 8(x-4)-2(x-3)+9x= | | 80=-39+c | | -6.8+-1.9= | | -113=-2x-3(-x+35) | | 3x-4=8x+16 | | 3m+v=-0.11+5v | | 2+1+f=-f+7f-2 | | 83=19+y | | -56x^2y^3/16x^4y^-1 | | 3x+14=98 | | 10(8)(x)=120 | | 48=-28+f | | -5(7-5)-8= | | s=3t^3-2t | | 1/4*1/9 | | -4(1-5b)=-124 | | -5(-5-7)+9= | | 0.5(x-1)=0.33(x+1) | | 20*-0.4= | | 2b/2+b/4-4/2=34/8 | | 2y^2=7y | | 2(9+5)-8= | | 62=-6x-2(-x-9) | | 4-20(-0.4)= | | 0=-16x^2+12-4x+3 |